PENGARUH LEVERAGE, PROFITABILITY, DAN FIRM SIZE TERHADAP KINERJA INTELLECTUAL CAPITAL - Maria Rosa; Crescentiano Agung Wicaksono (AKUNTANSI DEWANTARA, 2022)
We are currently entering the era of the industrial revolution 4.0 which is closely related to technology. Of course, this also requires companies to focus on knowledge. One if the things related to knowledge is intellectual capital. This study aims to examine the effect of leverage, profitability, and firm size on intellectual capital performance. The population used service companies listed on the Indonesia Stock Exchange for the period 2016-2019. The data used from the annual report of service companies obtained through www.idxx.co.id and also from the company’s website. Intellectual capital performance calculation uses the VAICTM formula developed by Pulic (2000). The result showed that leverage had no effect on intellectual capital performance. Two other variables, namely profitability and firm size affect the performace of intellectual capital.